2020
DOI: 10.1371/journal.pntd.0008247
|View full text |Cite|
|
Sign up to set email alerts
|

Association of NOD2 and IFNG single nucleotide polymorphisms with leprosy in the Amazon ethnic admixed population

Abstract: Leprosy is a chronic infectious disease, caused by Mycobacterium leprae, which affects skin and peripheral nerves. Polymorphisms in genes associated with autophagy, metabolism, innate and adaptive immunity confer susceptibility to leprosy. However, these associations need to be confirmed through independent replication studies in different ethnicities. The population from Amazon state (northern Brazil) is admixed and it contains the highest proportion of Native American genetic ancestry in Brazil. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
(69 reference statements)
0
23
0
Order By: Relevance
“…NUDT22 is a Mg 2+ -dependent UDP-glucose and UDP-galactose hydrolase( 64 ), while high glucose shows a negative effect in HIE like stroke( 65 ). CCDC122 potentially pro-inflammatory( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NUDT22 is a Mg 2+ -dependent UDP-glucose and UDP-galactose hydrolase( 64 ), while high glucose shows a negative effect in HIE like stroke( 65 ). CCDC122 potentially pro-inflammatory( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…NUDT22 is an Mg 2+ -dependent UDP-glucose and UDP-galactose hydrolase[44], while high glucose shows a negative effect in HIE like stroke[45]. CCDC122 potentially pro-inflammatory[46]. CIRP can effectively reduce cell death in the early stage of hypothermia therapy.…”
Section: Resultsmentioning
confidence: 99%
“…By applying unbiased WGS analysis on a family with monozygotic twins with extreme early-onset leprosy, we identified three coding variants in the LRRK2 and NOD2 genes as strong candidates for contributing to early-onset leprosy susceptibility. Rare and common variants in both genes had previously been associated with leprosy and leprosy reactions by candidate and genome-wide association studies (3,6,7,(24)(25)(26)(27)(28)(29)(30). Intriguingly, the same coding variants identified in the leprosy family have been implicated in reduced susceptibility to PD and CD (8).…”
Section: Discussionmentioning
confidence: 98%
“…S1P pathway and TRAIL signaling pathway have been extensively investigated as potential targets for treatments of multiple diseases. It has been reported that the bi-directional promoter region of PACRG and Parkin genes is associated with susceptibility to leprosy and several types of cancer, but the underlying mechanisms are still poorly elucidated [ 10 , 13 , 32 , 33 , 34 , 35 , 36 ]. Leprosy is a chronic infectious disease caused by Mycobacterium leprae , and clinical manifestations of leprosy are strongly correlated with the host’s immune responses [ 37 ].…”
Section: Discussionmentioning
confidence: 99%